A new strategy for large-scale synthesis of Na0.5Bi0.5TiO3 nanowires and their application in piezocatalytic degradation. Issue 11 (20th April 2021) - Huang, Rui; Wu, Jiang; Lin, Enzhu; Kang, Zihan; Qin, Ni; Bao, Dinghua
Abstract : Na0.5 Bi0.5 TiO3 nanowires prepared by the template hydrothermal method exhibited excellent piezocatalytic activity in the degradation of organic pollutants. Abstract : Developing new techniques that can synthesize one-dimensional piezoelectric materials on a large scale is of great significance for boosting piezocatalytic applications. In this work, we proposed a high-efficiency template hydrothermal method for large-scale synthesis of piezoelectric Na0.5 Bi0.5 TiO3 (NBT) nanowires. By ion-exchange with Bi 3+, Na2 Ti3 O7 template nanowires can be easily and entirely transformed to NBT. The piezocatalytic activity of the NBT nanowires was thoroughly investigated with respect to their capability to degrade typical organic pollutants, including Rhodamine B, methylene blue, methyl orange, tetracycline hydrochloride, phenol, and bisphenol A. The NBT nanowires exhibited the highest efficiency in piezocatalytic degradation of Rhodamine B, which was completely decomposed within 80 min (rate constant ∼0.0575 min −1 ). The electron spin resonance spin-trapping technique and active species capture experiments were employed to characterize free radicals. The present work is advantageous for the high yield of NBT nanowires and the excellent piezocatalytic performance. The reported template hydrothermal method can potentially be extended to the synthesis of other perovskite nanowires.